Study of Global Solar Radiation in Duhok Province - Kabao, Farhan Keti; Omar, Omar Salih (Science Journal of University of Zakho, 2022)
This paper studies and analyzes the ground-based global solar radiation (GSR) data available in the Dohuk governorate. The data was collected from the Meteorological Directorate in Duhok for six stations: Kani Masi, Bamarni, Amedi, Mangesh, Akre, and Semel. The highest monthly average values of GSR in Duhok were in June and July, and the lowest values were in December and January. Among all stations, Amedi has the highest value of the monthly mean of GSR (8.7041 kWh/m2/day) followed by Kani Masi at (8.5265), Mangesh at (8.3249), Bamarni at (8.072), Semel (7.0506) and finally Akre 6.1171(kWh/m2/day), while the lowest values of GSR were in December 2018 mostly, except for Semel was in December 2016. The annual mean of GSR in (kWh/m2/day) for these stations were 5.0168, 4.8311, 4.817, 4.7546, 4.3155, and 3.6183 for Amedi, Kani Masi, Mangesh, Bamarni, Semel, and Akre respectively. The monthly mean of the daily clearness index of the study area peaks is in the mid months of the year (May, June, July, August, and September). KT values experienced a dramatic decrease in March in all stations except Mangesh showed a slight increase. Among all the stations, Akre saw the lowest values in KT ranging from 0.32997 to 0.50686 with an annual average of 0.42443.